Effectiveness of silver diamine fluoride and glass ionomer cement combined with fluoride varnish in arresting dental caries among intellectually disabled individuals: A randomized controlled trial. (25th May 2021) - Mendiratta, Mansi; B.C., Manjunath; Kumar, Adarsh; Yadav, Vipul; Shyam, Radhey; Wig, Madhavi
Abstract: Aim: To assess the clinical effectiveness of 38% silver diamine fluoride (SDF) in arresting dental caries when compared to combination of fluoride‐containing glass ionomer cement (GIC) and fluoride varnish(FV) (5%) among intellectually disabled (ID) individuals. Methodology: A randomized controlled trial was conducted among ID ( n = 82) individuals, in permanent posterior teeth with Nyvad score 2 and 3 (active caries) of dental caries, randomly allocated to experimental arm (38% SDF) ( n = 41) and control arm (GIC along with FV) ( n = 41). The caries arrest rate and caries preventive fraction was observed at 6‐months among both groups. Results: The caries arrest rate was 94.5% with SDF and 90.1% with GIC and FV ( p = 0.405).The caries preventive fraction of SDF over GIC with FV was 45%, with hazard ratio (–0.588) at 6 months ( p = 0.292). The binary logistic regression revealed that the Odds of arresting caries in SDF group is two times when compared to GIC group with p value = 0.218 which is not significant. Conclusion: The present study concluded that the SDF is as clinically effective as combination of GIC and fluoride varnish in arresting caries. Further research and longer follow‐up required for more conclusive results.